PSYCHIATRIC MANIFESTATION AS PART OF PSEUDOBULBAR AFFECT IN POST-STROKE PATIENTS – CASE REPORT - Gunawan, Marco; Kurniawan, Fenny (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2026)
Introduction: Pseudobulbar affect (PBA) is a neurological disorder characterized by involuntary episodes of laughing or crying that are incongruent with emotional state. This condition is frequently underrecognized after stroke and may significantly impair quality of life, particularly in settings where first-line pharmacological therapy is unavailable. Methods: We report a case of a 53-year-old woman with a history of ischemic stroke who developed recurrent episodes of uncontrollable laughter and crying for five years. Clinical assessment included CNS-LS, PLACS, and MADRS scores, with follow-up conducted after pharmacological management. Results: During follow-up, a gradual reduction in the frequency and intensity of emotional outbursts was observed after treatment with sertraline. Improvement in depressive symptoms occurred alongside the reduction of pseudobulbar affect episodes. This therapeutic response represents an individual clinical observation rather than evidence of treatment efficacy. Discuss: This case highlights the clinical relevance of recognizing pseudobulbar affect in post-stroke patients and suggests that SSRIs may be considered as an alternative option in resource-limited settings. Conclusion: Careful clinical evaluation of emotional dysregulation after stroke is essential. Observational improvement in this case underscores the importance of accurate diagnosis and highlights the need for further studies to establish effective management strategies for pseudobulbar affect. Keywords: pseudobulbar affect, stroke, antidepressant.